Assessing Gender Disparity in Job Satisfaction: A Bayesian Approach - Shahren, Ahmad Zaidi Adruce; Donald, Stephen; Victoria, Jonathan (Human Resource Management Academic Research Society, 2021)
This study demonstrates the use of Bayesian independent samples t-test to illustrate gender disparity in job satisfaction. Results from this state-wide study involving over 4000 employees in private companies in Sarawak, Malaysia shows male employees are generally more satisfied in job satisfaction as compared to their female counterparts. This finding casts doubt on the contented female worker paradox, which refers to the notion that although women received fewer job-related benefits in the workplace, they are just as satisfied (or more satisfied) with their jobs. Poor reproducibility of the findings is causing more confusion on gender disparity in job satisfaction. Frequentist approaches have dominated the field of Psychology thus far. Prior researches on gender disparity were centred mainly based on p-values and null hypothesis significant testing (NHST). Instead of making an inference based on a cut-off value of 0.05, it is more intuitive and convincing to illustrate the weight of the evidence favouring a given hypothesis using likelihood ratio of one hypothesis to the other.